2024
DOI: 10.1111/apt.17892
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of MAFLD in general population: A large cross‐sectional study calls for concerted public health action

Tushar Prabhakar,
Manya Prasad,
Guresh Kumar
et al.

Abstract: SummaryBackgroundMetabolic associated fatty liver disease (MAFLD) is a relatively new term with limited studies done in South Asian population.AimTo determine prevalence and clinico‐epidemiological characteristics of MAFLD in general population.MethodsA cross‐sectional study was conducted in randomly selected regions across Delhi, India. Data were collected on socio‐demographic particulars, health status and lifestyle factors. Anthropometric measurements, transient elastography, and laboratory investigations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the research conducted by Dao et al, there was a higher prevalence of obesity MAFLD in females than males (62.6% vs. 47.6%; p < 0.001) 25 . Previous research has demonstrated that there were significantly more females than males with MAFLD in age subgroups older than 40 years and there was a sharp rise in the prevalence of MAFLD in perimenopausal and postmenopausal women 26 , 27 , a period during which the decrease in oestrogen levels can lead to fat redistribution and lead to metabolic disorders, including MAFLD 28 . Furthermore, abdominal obesity in women is a well-documented risk factor for polycystic ovary syndrome(PCOS) while a number of studies have suggested the close correlation between PCOS and NAFLD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted by Dao et al, there was a higher prevalence of obesity MAFLD in females than males (62.6% vs. 47.6%; p < 0.001) 25 . Previous research has demonstrated that there were significantly more females than males with MAFLD in age subgroups older than 40 years and there was a sharp rise in the prevalence of MAFLD in perimenopausal and postmenopausal women 26 , 27 , a period during which the decrease in oestrogen levels can lead to fat redistribution and lead to metabolic disorders, including MAFLD 28 . Furthermore, abdominal obesity in women is a well-documented risk factor for polycystic ovary syndrome(PCOS) while a number of studies have suggested the close correlation between PCOS and NAFLD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the indissociation between obesity, DM2, metabolic syndrome, MAFLD, and the brain-gut-liver axis is undeniable. This complex and not fully understood relationship is closely linked to the risk of hepatic fibrosis, which is aggravated with advancing age [36,37].…”
Section: Introductionmentioning
confidence: 99%